Alien research - Koch, Gini (Koch, Gini. Alien novels., 2013)
When rumors of a new super-drug surface, the FBI comes to Jeff and Kitty Katt-Martini for help. It becomes quickly apparent that the drug is merely the tip of a deadly iceberg and a much more insidious plan is underway involving Titan Security, Gaultier Enterprises, and YatesCorp. As newly discovered A-Cs and hybrids begin to surface, each with expanded and deadly talents, more and more signs point to a new evil genius who's using the A-Cs and their enemies both as guinea pigs. Then Area 51 and the Dulce Science Center go silent while Alpha Team, Airborne, and most of the worldwide A-C Security team are there for training. And if that's not bad enough, Centaurion Division is hit with more bad, and deadly, news: Chernobog the Ultimate, isn't a hacker myth, he's a real person -- and he's on the bad guys' side.